High-bending 3003-O aluminum alloy plate and preparation method thereof
By optimizing the composition design and hot rolling + annealing process of 3003 aluminum alloy, intermetallic compounds are formed as nucleation particles and grain size is refined, the problem of insufficient bending performance of 3003 aluminum alloy is solved, and a high bending performance aluminum alloy sheet is achieved.
Patent Information
- Application Number
- CN202311373999.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-23
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, the bending performance of 3003 aluminum alloy has not been effectively studied and improved, especially in the annealing process of hot-rolled sheets.
By optimizing the composition design of 3003 aluminum alloy, Ti and Sb elements were added in composite to form intermetallic compounds such as AlxTiy, AlxSby, Alx(Ti,Sb)y as nucleation particles, refine the grain size, and adopt a hot rolling + annealing process to control the annealing temperature and time to form a complete recrystallized structure.
The high bending performance of 3003-O aluminum alloy sheet was achieved, with a yield strength of 35-46MPa in the 0° direction, a tensile strength of 101-120MPa, an elongation of 37-50%, a bending radius of 0t and a bending angle of 180°C, and no orange peel phenomenon.
Smart Images

Figure CN119876696A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum alloy preparation, and specifically relates to a high-bending 3003-O aluminum alloy plate and a preparation method thereof. Background Art
[0002] 3xxx series aluminum alloy refers to pure aluminum with Mn and other trace elements added. Compared with pure aluminum, 3xxx series aluminum alloys have slightly lower corrosion resistance, but higher specific strength, good plasticity and weldability. Among them, 3003 alloy is widely used in battery housings, heat exchangers, containers and other fields due to its excellent corrosion resistance and welding performance.
[0003] In large-scale industrial production, hot rolling is generally used to break up the coarse grains in the casting state, reduce casting defects, and generate a large number of dislocations to improve the mechanical properties of the alloy. However, as the rolling continues, the forming ability of the sheet decreases sharply due to the effect of work hardening, affecting subsequent deformation processes such as stamping.
[0004] In order to improve the plasticity of the alloy material, annealing the aluminum alloy sheet after hot rolling can reduce the adverse effects of work hardening, obtain excellent comprehensive mechanical properties, and improve its forming ability.
[0005] In order to obtain 3003 aluminum alloy strip suitable for power battery shell, Chinese patent CN109487132A discloses "aluminum alloy strip for power battery shell and its manufacturing method". In order to improve the stamping performance of 3003 alloy, the patent adds a small amount of Ti element while adjusting the Mg / Si ratio to refine the grain size. After melting, hot rolling and cold rolling, the obtained 3003 alloy strip is placed in an annealing furnace for annealing at 380℃×2h, 380℃×6h, 400℃×3h, and 410℃×3h. The tensile strength of the annealed 3003 alloy strip is ≥130MPa, which has exceeded the mechanical properties (i.e. 95~135MPa) requirements of 3003-O in GB / T3880.2.
[0006] In order to adjust the mechanical properties of 3003 alloy, Chinese patent CN 105510549 A discloses "a method for testing the influence of Mn on the performance of 3003 aluminum alloy", which improves the mechanical properties of 3003 alloy by adjusting the Mn content. The results show that the tensile strength of the cold-rolled sheet with a thickness of 0.88 mm after annealing at 220-320℃×1h is ≥181MPa, which exceeds the mechanical property requirements of 3003-O in GB / T 3880.2.
[0007] In order to further study the appropriate annealing process system for 3003 alloy, the document "Production Process of 3003-O Aluminum Alloy Strip" was published. By studying the production process of 3003-O for mobile phone battery cases, it was found that the suitable annealing temperature range for 3003 cold-rolled strip with a finished thickness of 0.6 mm is 340-360°C. The yield strength in this range is 51 MPa, the tensile strength is 120 MPa, and the elongation is 33%, which meets the mechanical property requirements of 3003-O in GB / T 3880.2. However, the document does not mention the annealing time and the annealing process of 3003 alloy hot-rolled plate, and does not mention the bending performance.
[0008] In order to improve the deep drawing and tensile properties of 3003 aluminum alloy sheets, Chinese patent CN 113061786A discloses "Rare earth aluminum strip for stretching battery shells", which improves the melt quality by adding 0.02-0.04% Ti and 0.2-0.3% La to the alloy melt. After melting, hot rolling and cold rolling, the obtained 3003 alloy sheet is placed in an annealing furnace for annealing at 360-365℃×5h. Its tensile strength is 123MPa and its elongation is 35%, which meets the mechanical property requirements of 3003-O in GB / T3880.2. However, the addition of rare earth La in this patent increases the production cost, and the 5h annealing time delays the production rhythm, which is not conducive to industrial production.
[0009] In summary, the current patents and literature mainly consider the mechanical properties of 3003 aluminum alloy, and no research is conducted on the bending performance. Relevant treatments are carried out on 3003 cold-rolled sheets and strips in order to obtain 3003-O sheets and strips with good performance. However, there is no literature or patent reporting on the annealing process of 3003 alloy hot-rolled sheets. Summary of the invention
[0010] The object of the present invention is to provide a high-bending 3003-O aluminum alloy plate and a preparation method thereof. The aluminum alloy plate meets the mechanical property requirements of Part 2 of GB / T 3880.2-2012 general industrial aluminum and aluminum alloy plates and strips, and also has high bending resistance; the 0° direction yield strength of the aluminum alloy plate is 35-46MPa, the tensile strength is 101-120MPa, the elongation is 37-50%, and the plate does not crack and has no orange peel phenomenon when the bending radius reaches 0t and the bending angle is 180°.
[0011] To achieve the above object, the technical solution of the present invention is:
[0012] A high-bending 3003-O aluminum alloy plate, whose chemical composition weight percentage is: Si: 0.23-0.27%, Fe: 0.47-0.53%, Cu: 0.06-0.11%, Mn: 1.06-1.14%, Zn≤0.012%, Ti: 0.02-0.03%, Sb: 0.02-0.15%, and the rest includes Al and other inevitable impurities, the total amount of impurities is ≤0.15%, and it is necessary to simultaneously meet the following conditions: 1≤Sb / Ti≤5.
[0013] Furthermore, the remainder is Al and other inevitable impurities.
[0014] The aluminum alloy sheet of the present invention is composed of uniformly distributed intermetallic compounds Al x Ti y 、Al x Sb y 、Al x (Ti,Sb) y As a recrystallization nucleation point, Al x Sb y 、Al x (Ti,Sb) y The size of a single particle is between 200 and 500 nm. x Ti y The individual particle size is between 1.8 and 4.6 μm.
[0015] The grain structure of the aluminum alloy plate of the present invention is a recrystallized structure with an aspect ratio of 2 to 12, and a grain width of 40 to 212 μm.
[0016] The aluminum alloy plate of the present invention has a yield strength of 35-46 MPa in the 0° direction, a tensile strength of 101-120 MPa, an elongation of 37-50%, and no cracking or orange peel phenomenon when the bending radius reaches 0t and the bending angle is 180°.
[0017] In the composition design of the 3003-O aluminum alloy sheet of the present invention:
[0018] Mn: As the main controlling element of 3xxx series aluminum-manganese alloy, it can improve the strength, plasticity and processing performance of the alloy. If the content is too high, a large amount of brittle compound MnAl6 will be formed, which will cause the alloy to crack easily when deformed and reduce plasticity; if the content is too low, the mechanical properties will be reduced. Therefore, the present invention controls the Mn element content to 1.06-1.14%.
[0019] Si: can enhance casting performance, but it forms Al with Mn 12 Mn3Si2 impurity phase, if Fe and Si exist at the same time, will form a skeleton-like α-Al 12Fe3Si2 or needle-shaped β-Al9Fe2Si2 phases are not conducive to pressure processing. Therefore, the present invention controls the Si element content to 0.23-0.27% while ensuring casting performance.
[0020] Fe: An appropriate amount of Fe can play a role in grain refinement, but in aluminum-manganese alloys, the sum of the content of Fe and Mn should be guaranteed not to be greater than 1.8%, otherwise a large number of coarse (Fe, Mn) Al6 flake phases will be formed, reducing the mechanical properties and process properties of the alloy. Therefore, the present invention controls the Fe content to 0.47-0.53%.
[0021] Cu: The addition of Cu element can improve the mechanical properties, but excessive addition will reduce the corrosion resistance of the alloy. In order to ensure the mechanical properties of the finished alloy, the present invention controls the Cu content to 0.06-0.11%.
[0022] Zn: The Zn element has no significant effect on the mechanical properties and corrosion resistance of 3xxx series aluminum alloys, but will reduce its welding performance. Therefore, the present invention controls the Zn content to below 0.012%.
[0023] Ti: Ti is a commonly used additive element in aluminum alloys. Ti and Al form Al x Ti y Such intermetallic compounds can serve as nucleation cores to refine the grain size of the alloy. However, excessive addition will lead to Al x Ti y The aggregation of intermetallic compounds such as Ti affects the refinement effect and processing effect. Therefore, the Ti content is controlled within 0.02-0.03% in the present invention.
[0024] Sb: Sb is mostly used in Al-Si casting alloys. The present invention adds Sb and Ti elements to enhance the grain refinement effect of the casting process and annealing process. The Sb content is controlled between 0.02% and 0.15%, and the mass ratio of Sb / Ti is controlled between 1 and 5 to form Al x Ti y 、Al x Sb y 、Al x (Ti,Sb) y Intermetallic compounds such as aluminum alloys act as nucleation particles to improve the nucleation ability of aluminum alloys, refine the grain size, and thus improve the bending resistance of the product.
[0025] The present invention optimizes the traditional 3003 alloy component system, and adds Ti and Sb elements on the basis of the traditional 3003 alloy component system to form Al x Ti y 、Al xSb y 、Al x (Ti,Sb) y Intermetallic compounds such as 2-H2O serve as nucleation particles of aluminum alloy, which improve the nucleation ability of aluminum alloy and the grain refinement effect of aluminum alloy. The grain size of 3003 alloy is further refined, and the grains are transformed from fibrous structures with an aspect ratio of 100 to 1000 to recrystallized structures with an aspect ratio of 2 to 12, and the grain width is 40 to 212 μm. The mechanical properties of aluminum alloy meet the requirements of Part 2 of GB / T 3880.2-2012 General Industrial Aluminum and Aluminum Alloy Plates and Strips, and also have high bending performance.
[0026] The present invention also provides a method for preparing a high-bend 3003-O aluminum alloy sheet, comprising the following steps:
[0027] 1) Melting and casting
[0028] According to the above ingredients, smelting and casting are performed to obtain an ingot;
[0029] 2) Heating and homogenization
[0030] Heating temperature 480~500℃, heating time 2~4h;
[0031] 3) Hot rolling
[0032] Hot rough rolling and hot finishing rolling are carried out in sequence to obtain hot rolled coils, the reduction rate of the last stand of hot finishing rolling is controlled at 50-60%, and the coiling temperature is 330±5°C;
[0033] 4) Annealing
[0034] Annealing temperature: 375~385℃, annealing time 1.5~3.0h.
[0035] Further, in step 1), the obtained ingot is sawn and milled, the ingot gate is not sawed, the sawing length of the ingot lead head is ≥200mm, the milling amount of the large surface of the ingot is ≥12mm, and the milling amount of the side of the ingot is ≥8mm.
[0036] Preferably, in step 3), the thickness of the hot rolled coil is 4.5 to 6.0 mm.
[0037] Preferably, in step 4), the annealing time is 1.8 to 2.2 hours.
[0038] The present invention heats the ingot to 480-500°C for 2-4 hours for homogenization to ensure that the Al2O3 formed by Ti and Sb elements x Ti y 、Al x Sb y 、Al x (Ti,Sb) yIntermetallic compounds are dispersed.
[0039] During the hot rolling process, the reduction rate of the last stand is controlled at 50-60% to fully deform the core of the material. x Ti y 、Al x Sb y 、Al x (Ti,Sb) y Intermetallic compounds such as Al and Mg are evenly distributed inside the plate as recrystallization nucleation points. x Sb y 、Al x (Ti,Sb) y The single particle size is between 200 and 500 nm, Al x Ti y The single particle size is between 1.8-4.6μm, making Al x Ti y 、Al x Sb y 、Al x (Ti,Sb) y Intermetallic compounds such as ferrite can exert strong nucleation ability. The coiling temperature is controlled at 325-335℃ to ensure that the product is softened enough when coiling without cracking.
[0040] Control annealing temperature: 375 ~ 385 ℃, annealing time 1.8 ~ 2.2h, to ensure that the alloy can be Al x Ti y 、Al x Sb y 、Al x (Ti,Sb) y The intermetallic compounds such as ferrite and tantalum are used as nucleation particles to refine the grain size of 3003 alloy. The grain structure is transformed from a fibrous structure with an aspect ratio of 100 to 1000 to a recrystallized structure with an aspect ratio of 2 to 12. The grain width is 40 to 212 μm, and a complete recrystallized structure is formed, thereby improving the bending resistance of the alloy while ensuring that the mechanical properties of the alloy meet the requirements. When the annealing temperature is lower than 375°C and the holding time is too short, fibrous structures exist in the alloy structure and the structure cannot be completely transformed into recrystallized structures. When the annealing temperature exceeds 385°C, the recrystallized structure coarsens.
[0041] After the hot-rolled coil is cooled after annealing, the plate is cut into the required size using a cross-cutting machine, and samples are taken after cross-cutting to test product performance.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] In terms of composition design, the present invention optimizes the traditional 3003 alloy composition system, adds Ti and Sb elements in combination, and controls 1≤Sb / Ti≤5 to form an Al-based alloy. x Ti y 、Al x Sb y 、Al x (Ti,Sb) y The intermetallic compounds such as Mn and Mg serve as nucleation points of aluminum alloy, improve the nucleation ability of aluminum alloy, enhance the effect of grain refinement of aluminum alloy, refine the grain size of 3003 alloy, and transform the grain from fibrous structure with aspect ratio of 100-1000 to recrystallized structure with aspect ratio of 2-12, and the grain width is 40-212μm, so that the mechanical properties of aluminum alloy meet the requirements of GB / T 3880.2-2012 Part 2 of general industrial aluminum and aluminum alloy plates and strips, and have high bending performance. The traditional 3003 series aluminum alloy improves the mechanical properties by adding higher Mn, and only considers the mechanical properties of the alloy without considering the requirements of bending performance.
[0044] The present invention combines the process flow of hot rolling + annealing on the basis of component design to make the formed Al x Ti y 、Al x Sb y 、Al x (Ti,Sb) y Intermetallic compounds such as Al x Sb y 、Al x (Ti,Sb) y The single particle size is between 200 and 500 nm, Al x Ti y The single particle size is between 1.8 and 4.6 μm, which maximizes the strong nucleation ability of the nucleation particles, refines the grain size of the 3003 alloy, and transforms the grain structure from a fibrous structure with an aspect ratio of 100 to 1000 to a recrystallized structure with an aspect ratio of 2 to 12. The grain width is 40 to 212 μm, and a complete recrystallized structure is formed. The mechanical properties of the alloy can meet the requirements without the need for cold rolling, and the bending resistance of the alloy is improved.
[0045] The aluminum alloy plate obtained by the present invention has a yield strength of 35-46 MPa in the 0° direction, a tensile strength of 101-120 MPa, an elongation of 37-50%, and no cracking or orange peel phenomenon when the bending radius reaches 0t and the bending angle is 180°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is a metallographic structure photograph of the aluminum alloy plate of Example 1 of the present invention.
[0047] Figure 2 This is a metallographic structure photograph of the aluminum alloy plate of Example 2 of the present invention.
[0048] Figure 3 This is a metallographic structure photograph of the aluminum alloy plate of Example 3 of the present invention.
[0049] Figure 4 This is a metallographic structure photograph of the aluminum alloy plate of Example 4 of the present invention.
[0050] Figure 5 This is a metallographic structure photograph of the aluminum alloy plate of Example 5 of the present invention.
[0051] Figure 6 This is a metallographic structure photograph of the aluminum alloy plate of Example 6 of the present invention.
[0052] Figure 7 This is a metallographic structure photograph of the aluminum alloy plate of Example 7 of the present invention.
[0053] Figure 8 This is the metallographic structure photo of the aluminum alloy plate of comparative example 1.
[0054] Fig. 9 This is the metallographic structure photo of the aluminum alloy plate of comparative example 2.
[0055] Fig.10 This is the metallographic structure photo of the aluminum alloy plate of comparative example 3.
[0056] Fig.11 This is the metallographic structure photo of the aluminum alloy plate of comparative example 4.
[0057] Fig.12 This is the metallographic structure photo of the aluminum alloy plate of comparative example 5.
[0058] Fig.13 This is the metallographic structure photo of the aluminum alloy plate of comparative example 6.
[0059] Fig.14 This is the metallographic structure photo of the aluminum alloy plate of comparative example 7. DETAILED DESCRIPTION
[0060] The present invention will be further described below in conjunction with the embodiments and drawings.
[0061] The aluminum alloy composition of the embodiment of the present invention is shown in Table 1, and the remainder of the composition includes Al and other inevitable impurities; the process parameters of the embodiment of the present invention and the comparative example are shown in Table 2. Table 3 shows the performance parameters of the embodiment of the present invention and the comparative example.
[0062] The embodiment of the present invention adopts a vacuum induction + electroslag smelting process.
[0063] Example 1, A1x Ti y 、Al x Sb y 、Al x (Ti,Sb) y The intermetallic compounds are evenly dispersed in the 3003 aluminum alloy matrix. x Sb y 、Al x (Ti,Sb) y The average size of a single intermetallic compound particle is 368nm. x Ti y The average size of a single particle is 1.8 μm. Figure 1 This is a metallographic microstructure photo of the longitudinal section of the aluminum alloy sample of Example 1 of the present invention. It can be seen from the photo that the grain structure is transformed from an elongated fibrous structure to a recrystallized structure with an aspect ratio of 2-6, and the grain width is 40-110 μm. The mechanical properties meet the mechanical property requirements of 3003-O alloy in GB / T 3880.2. At the same time, the bending performance of the product at a bending angle of 180° under a bending radius of 0t was measured, and the product did not crack and had no orange peel phenomenon.
[0064] In Example 2, Al x Ti y 、Al x Sb y 、Al x (Ti,Sb) y The intermetallic compounds are evenly dispersed in the 3003 aluminum alloy matrix. x Sb y 、Al x (Ti,Sb) y The average size of a single particle of the intermetallic compound is 493nm. x Ti y The average size of a single particle is 2.2 μm. Figure 2 This is a metallographic structure photo of the longitudinal section of the aluminum alloy sample of Example 2 of the present invention. It can be seen from the photo that the grain structure is transformed from a slender fibrous structure to a recrystallized structure with an aspect ratio of 3-6, and the grain width is 77-130μm. The mechanical properties meet the mechanical property requirements of 3003-O alloy in GB / T 3880.2. At the same time, the bending performance of the product at a bending angle of 180° under a bending radius of 0t was measured, and the product did not crack and had no orange peel phenomenon.
[0065] In Example 3, Al x Ti y 、Al x Sb y 、Al x (Ti,Sb) yThe intermetallic compounds are evenly dispersed in the 3003 aluminum alloy matrix. x Sb y 、Al x (Ti,Sb) y The average size of a single intermetallic compound particle is 325nm. x Ti y The average size of a single particle is 2.6 μm. Figure 3 This is a metallographic microstructure photo of the longitudinal section of the aluminum alloy sample of Example 3 of the present invention. It can be seen from the photo that the grain structure is transformed from a slender fibrous structure to a recrystallized structure with an aspect ratio of 3 to 7, and the grain width is 105 to 135 μm. The mechanical properties meet the mechanical property requirements of 3003-O alloy in GB / T 3880.2. At the same time, the bending performance of the product at a bending angle of 180° under a bending radius of 0t was measured, and the product did not crack and had no orange peel phenomenon.
[0066] In Example 4, Al x Ti y 、Al x Sb y 、Al x (Ti,Sb) y The intermetallic compounds are evenly dispersed in the 3003 aluminum alloy matrix. x Sb y 、Al x (Ti,Sb) y The average size of a single particle of the intermetallic compound is 293nm. x Ti y The average size of a single particle is 3.2 μm. Figure 4 This is a metallographic structure photo of the longitudinal section of the aluminum alloy sample of Example 4 of the present invention. It can be seen from the photo that the grain structure is transformed from a slender fibrous structure to a recrystallized structure with an aspect ratio of 3 to 9, and the grain width is 80-140μm. The mechanical properties meet the mechanical property requirements of 3003-O alloy in GB / T 3880.2. At the same time, the bending performance of the product at a bending angle of 180° under a bending radius of 0t was measured, and the product did not crack and had no orange peel phenomenon.
[0067] In Example 5, Al x Ti y 、Al x Sb y 、Al x (Ti,Sb) y The intermetallic compounds are evenly dispersed in the 3003 aluminum alloy matrix. x Sb y 、Al x (Ti,Sb) yThe average size of a single particle of the intermetallic compound is 268nm. x Ti y The average size of a single particle is 3.7 μm. Figure 5 This is a metallographic structure photo of the longitudinal section of the aluminum alloy sample of Example 5 of the present invention. It can be seen from the photo that the grain structure is transformed from a slender fibrous structure to a recrystallized structure with an aspect ratio of 5 to 11, and the grain width is 95 to 187 μm. The mechanical properties meet the mechanical property requirements of 3003-O alloy in GB / T 3880.2. At the same time, the bending performance of the product at a bending angle of 180° under a bending radius of 0t was measured, and the product did not crack and had no orange peel phenomenon.
[0068] In Example 6, Al x Ti y 、Al x Sb y 、Al x (Ti,Sb) y The intermetallic compounds are evenly dispersed in the 3003 aluminum alloy matrix. x Sb y 、Al x (Ti,Sb) y The average size of a single particle of the intermetallic compound is 227nm. x Ti y The average size of a single particle is 4.3 μm. Figure 6 This is a metallographic structure photo of the longitudinal section of the aluminum alloy sample of Example 6 of the present invention. It can be seen from the photo that the grain structure is transformed from a slender fibrous structure to a recrystallized structure with an aspect ratio of 7 to 11, the grain aspect ratio increases, and the grain width is 104-208μm. The mechanical properties meet the mechanical property requirements of 3003-O alloy in GB / T 3880.2. At the same time, the bending performance of the product at a bending angle of 180° under a bending radius of 0t was measured, and the product did not crack and had no orange peel phenomenon.
[0069] In Example 7, Al x Ti y 、Al x Sb y 、Al x (Ti,Sb) y The intermetallic compounds are evenly dispersed in the 3003 aluminum alloy matrix. x Sb y 、Al x (Ti,Sb) y The average size of a single particle of the intermetallic compound is 204nm. x Ti y The average size of a single particle is 4.6 μm. Figure 7The metallographic structure photo of the longitudinal section of the aluminum alloy sample of Example 7 of the present invention shows that the grain structure is transformed from an elongated fibrous structure to a recrystallized structure with an aspect ratio of 7 to 12, and the grain width is 121 to 212 μm. The mechanical properties meet the mechanical property requirements of 3003-O alloy in GB / T 3880.2. At the same time, the bending performance of the product at a bending angle of 180° under a bending radius of 0t was measured, and the product did not crack and had no orange peel phenomenon.
[0070] Comparative Example 1: No Sb element is added, only Al x Ti y The intermetallic compounds are uniformly dispersed in the finished 3003 aluminum alloy matrix, and the average size of a single particle is 5.2 μm. Although the process control is within the scope of the present invention, Figure 8 From the metallographic structure photo of the longitudinal section of the aluminum alloy sample of Comparative Example 1, it can be seen that its grain structure is composed of a transformation of an elongated fibrous structure and a recrystallized structure with an aspect ratio of 7-8, and the grain width reaches 220μm. Its yield strength at room temperature is 50±1MPa, its tensile strength is 125±3MPa, and its elongation is 32±1%. It has not completely softened, and meets the mechanical property requirements of 3003-O alloy in GB / T 3880.2. At the same time, the bending performance of the 180° bending angle under a bending radius of 0t was measured. Although the product did not crack, the orange peel phenomenon was serious.
[0071] Comparative Example 2: Ti addition is too low, and Sb / Ti is too high. x Sb y Evenly dispersed in the 3003 aluminum alloy matrix, Al x Sb y The average size of individual intermetallic compound particles is 736 nm. Although the process control is within the scope of the present invention, Fig. 9 From the metallographic microstructure of the longitudinal section of the aluminum alloy sample in Comparative Example 2, it can be seen that its grain structure is transformed from an elongated fibrous structure to a recrystallized structure with an aspect ratio of 6-9, and the grain width reaches 233μm. Although it meets the mechanical property requirements of 3003-O alloy in GB / T3880.2, when its bending performance at a bending angle of 180° under a bending radius of 0t is measured, although the product does not crack, the orange peel phenomenon is serious.
[0072] Comparative Example 3: Sb addition is too high, and Sb / Ti is too high. x Ti y 、Al x Sb y 、Al x (Ti,Sb) y The intermetallic compounds are evenly dispersed in the 3003 aluminum alloy matrix.x Sb y 、Al x (Ti,Sb) y The average size of a single particle of the intermetallic compound is 687nm. x Ti y The average size of individual particles is 2.2 μm. Although process control is within the scope of the present invention, Fig.10 From the metallographic structure photo of the longitudinal section of the aluminum alloy sample of Comparative Example 3, it can be seen that its grain structure is composed of elongated fibrous structure and recrystallized structure with an aspect ratio of 6-12, and the maximum grain width can reach 285μm. Although it meets the mechanical property requirements of 3003-O alloy in GB / T3880.2. However, when measuring its bending performance at a bending angle of 180° under a bending radius of 0t, although the product does not crack, the orange peel phenomenon is serious.
[0073] Comparative Example 4: Sb / Ti is too high, Al x Ti y 、Al x Sb y 、Al x (Ti,Sb) y The intermetallic compounds are evenly dispersed in the 3003 aluminum alloy matrix. x Sb y 、Al x (Ti,Sb) y The average size of a single particle of the intermetallic compound is 73nm. x Ti y The average size of individual particles is 2.1 μm. Although process control is within the scope of the present invention, Fig.11 From the metallographic microstructure photograph of the longitudinal section of the aluminum alloy sample of Comparative Example 4, it can be seen that its grain structure is composed of elongated fibrous structures. Although it meets the mechanical property requirements of 3003-O alloy in GB / T 3880.2, when its bending performance at a bending angle of 180° under a bending radius of 0t is measured, although the product does not crack, the orange peel phenomenon is serious.
[0074] Comparative Example 5: The homogenization temperature is too low, Al x Ti y 、Al x Sb y 、Al x (Ti,Sb) y The intermetallic compounds are evenly dispersed in the matrix of the 3003 aluminum alloy product, but Al x Sb y 、Al x (Ti,Sb) yThe average size of a single particle of the intermetallic compound is 603nm. x Ti y The average size of a single particle is 2.0 μm. Although the composition is controlled within the scope of the present invention, Fig.12 From the metallographic microstructure photograph of the longitudinal section of the aluminum alloy sample of Comparative Example 5, it can be seen that its grain structure is composed of elongated fibrous structures. Although it meets the mechanical property requirements of 3003-O alloy in GB / T 3880.2, when the bending performance of the product at a bending angle of 180° under a bending radius of 0t is measured, slight cracking occurs in the product.
[0075] Comparative Example 6: The last stand hot rolling pass reduction rate is too low, Al x Ti y 、Al x Sb y 、Al x (Ti,Sb) y The intermetallic compounds are evenly dispersed in the 3003 aluminum alloy matrix. x Sb y 、Al x (Ti,Sb) y The average size of a single particle of the intermetallic compound is 707nm. x Ti y The average size of a single particle is 2.2 μm. Although the composition is controlled within the scope of the present invention, Fig.13 From the metallographic microstructure photograph of the longitudinal section of the aluminum alloy sample of Comparative Example 6, it can be seen that its grain structure is composed of elongated fibrous structures. Although it meets the mechanical property requirements of 3003-O alloy in GB / T 3880.2, when its bending performance at a bending angle of 180° under a bending radius of 0t is measured, the product has slight cracking.
[0076] Comparative Example 7: The annealing temperature is too low, Al x Ti y 、Al x Sb y 、Al x (Ti,Sb) y The intermetallic compounds are evenly dispersed in the 3003 aluminum alloy matrix. x Sb y 、Al x (Ti,Sb) y The average size of a single particle of the intermetallic compound is 209nm. x Ti y The average size of a single particle is 1.9 μm. Although the composition is controlled within the scope of the present invention, Fig.14From the metallographic microstructure photograph of the longitudinal section of the aluminum alloy sample of Comparative Example 7, it can be seen that its grain structure is composed of elongated fibrous structures. Although it meets the mechanical property requirements of 3003-O alloy in GB / T 3880.2, when the bending performance of the product at a bending angle of 180° under a bending radius of 0t is measured, slight cracking occurs in the product.
[0077]
[0078]
[0079]
Claims
1. A high-bending 3003-O aluminum alloy plate, whose chemical composition weight percentage is: Si: 0.23-0.27%, Fe: 0.47-0.53%, Cu: 0.06-0.11%, Mn: 1.06-1.14%, Zn≤0.012%, Ti: 0.02-0.03%, Sb: 0.02-0.15%, and the rest includes Al and other inevitable impurities, the total amount of impurities is ≤0.15%, and it is necessary to simultaneously meet the following conditions: 1≤Sb / Ti≤5.
2. The high-bend 3003-O aluminum alloy sheet according to claim 1, characterized in that: The rest is Al and other inevitable impurities.
3. The high-bend 3003-O aluminum alloy sheet according to claim 1 or 2, characterized in that: The aluminum alloy sheet is composed of uniformly distributed intermetallic compounds Al x Ti y 、Al x Sb y 、Al x (Ti,Sb) y As a recrystallization nucleation point, Al x Sb y 、Al x (Ti,Sb) y The size of a single particle is between 200 and 500 nm. x Ti y The individual particle size is between 1.8 and 4.6 μm.
4. The high-bend 3003-O aluminum alloy sheet according to claim 1, 2 or 3, characterized in that: The grain structure of the aluminum alloy plate is a recrystallized structure with an aspect ratio of 2 to 12, and a grain width of 40 to 212 μm.
5. The high-bend 3003-O aluminum alloy sheet according to claim 1, 2, 3 or 4, characterized in that: The aluminum alloy plate has a yield strength of 35-46 MPa in the 0° direction, a tensile strength of 101-120 MPa, an elongation of 37-50%, and no cracking or orange peel phenomenon when the bending radius reaches 0t and the bending angle is 180°.
6. A method for preparing the high-bend 3003-O aluminum alloy sheet as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: 1) Melting and casting Melting and casting the composition according to claim 1 or 2 to obtain an ingot; 2) Heating and homogenization Heating temperature 480~500℃, heating time 2~4h; 3) Hot rolling Hot rough rolling and hot finishing rolling are carried out in sequence to obtain hot rolled coils, the reduction rate of the last stand of hot finishing rolling is controlled at 50-60%, and the coiling temperature is 330±5°C; 4) Annealing Annealing temperature is 375-385°C, and annealing time is 1.5-3.0h.
7. The preparation method according to claim 6, characterized in that: In step 1), the obtained ingot is sawed and milled, the ingot gate is not sawed, the sawing length of the ingot lead head is ≥200mm, the milling amount of the large surface of the ingot is ≥12mm, and the milling amount of the side of the ingot is ≥8mm.
8. The preparation method according to claim 6, characterized in that: In step 3), the thickness of the hot rolled coil is 4.5 to 6.0 mm.
9. The preparation method according to claim 6, characterized in that: In step 4), the annealing time is 1.8 to 2.2 hours.
Citation Information
Patent Citations
Method for testing influence of Mn on performance of 3003 aluminum alloy
CN105510549A
Aluminum alloy strip for power battery shell and manufacturing method thereof
CN109487132A
Rare earth aluminum strip for stretch forming of battery shell
CN113061786A